A perspective on muscle phenotyping in musculoskeletal research - Foessl, Ines; Ackert-Bicknell, Cheryl L; Kague, Erika; Laskou, Faidra; Jakob, Franz; Karasik, David; Obermayer-Pietsch, Barbara; Co-authors; Alonso, Nerea; Bjørnerem, Åshild; Brandi, Maria Luisa; Busse, Björn; et al. (United States, 2025)
Musculoskeletal research should synergistically investigate bone and muscle to inform approaches for maintaining mobility and to avoid bone fractures. The relationship between sarcopenia and osteoporosis, integrated in the term 'osteosarcopenia', is underscored by the close association shown between these two conditions in many studies, whereby one entity emerges as a predictor of the other. In a recent workshop of Working Group (WG) 2 of the EU Cooperation in Science and Technology (COST) Action 'Genomics of MusculoSkeletal traits Translational Network' (GEMSTONE) consortium (CA18139), muscle characterization was highlighted as being important, but currently under-recognized in the musculoskeletal field. Here, we summarize the opinions of the Consortium and research questions around translational and clinical musculoskeletal research, discussing muscle phenotyping in human experimental research and in two animal models: zebrafish and mouse.